A BOOK REVIEW: TEACIDNG ENGLISH WITH CIDLD-CENTERED APPROACH AND LESSON TO CIDLDREN IN ASIA - Heny Hartono (Soegijapranata Catholic University, 2010)
As written by its author at the preface of the book, this book is written as a guidebook for English teachers in Asia countries. Based on his own experiences in teaching English to children in Japan, David Paul, the author of the book, is offering some practical guides to deal with English classes in Asia. Teaching English in Asia is challenging for hoth English native teachers and local English teachers due to some hard facts such as the teachers' knowledge about their English classes and materials, Asian children's nature and the English learners' environment.